Participation in the community context: water technical board. Is it a democratic model capable of combating basic environmental problems? (Dissertare, 2017)
The study arises from investigations on the meaning of participation in the community context, in the Water Technical Boards from  "Las Brisas del Paraíso", located at the Cota 905, of the Libertador municipality, in Caracas;  and the Water Technical Boards from "Las Juanas" located at Juan de Villegas of the Iribarren municipality, in Barquisimeto, Lara State. The objective of the study is to know the meaning of participation in the community context. Also, new questions are presented such as: Are the Water Technical Boards (WTBs) a factor in the development of participatory democracy? Does the communication among the members of these movements favor the conscious use of water resources? Participation in WTBs is activated due to: the high cost of water, the unequal distribution of resources in the country, an intense process of exclusion, the advance of poverty and inequality. For the year 2012, 8,409 WTBs are counted in Venezuela, developing 1,501 projects, with a completed execution of 74.4%, while 25.6% are in the process of being executed. When calibrating the possibilities for participatory democracy offered by the WTBs, it is necessary to consider, among other aspects, the improvements in infrastructure that occur through the implementation of the projects they execute, since more than 2.8 million inhabitants get benefit from this initiative.
Keywords: water; water technical boards; woman; participatory democracy